2017
DOI: 10.1136/bmjopen-2016-014854
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of hospital separations among people who inject drugs in Australia: 2008–2013

Abstract: ObjectivesInjecting drug use is a persistent behaviour that increases the risk of morbidities and mortality. We assessed the burden of hospital separations among people who inject drugs (PWID), the excess compared to the general population and characteristics of separations associated with frequent use.DesignProspective cohort study.SettingAll public and private hospitals in Victoria.Participants757 community-based PWID with hospital separations between January 2008 and June 2013 identified through record link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…All infections, and particularly pneumonias, were important causes of health‐care utilization in HIV‐positive opiate users . Infections were less important causes of health‐care utilization in Australia . Traumas, injuries and mental health problems were important causes of ED utilization and hospital admission in all countries .…”
Section: Resultsmentioning
confidence: 99%
“…All infections, and particularly pneumonias, were important causes of health‐care utilization in HIV‐positive opiate users . Infections were less important causes of health‐care utilization in Australia . Traumas, injuries and mental health problems were important causes of ED utilization and hospital admission in all countries .…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous drug use per se causes many health problems and therefore might accelerate the progression of immunodeficiency [39,40]. Furthermore, IVDUs have repeatedly been associated with low level of responsibility towards their health, and hesitation to seek for medical help, what puts them at high risk for disease progression [41][42][43]. However, considering that majority of IVDUs in our study were undergoing treatment for addiction, which improves their awareness and responsibility towards health and socialization, other causes for rapid progression to AIDS in HIV/HCV coinfected patients should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention opportunities are, however, not restricted to specialist mental health services. Australian research exploring the use of tertiary health services among PWID found PWID to be frequent users of emergency department (ED) and tertiary healthcare services and that ED presentations and hospital separations were most commonly related to mental and behavioural disorders (Nambiar et al, 2018; Nambiar et al, 2017). Similarly, a study of ambulance attendances among recently released prisoners found that one in twelve attendances involved self-harm or self-harm/suicidal ideation (Borschmann, Young, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%